Pengaruh Harga Dan Brand Awareness Terhadap Keputusan Pembelian Bittersweet By Najla - Maghda Fauziah Ainurrokhmah; Nur Aini Anisa; Aisyah Darti Megasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of price on purchasing decisions of Bittersweet by Najla, to determine the effect of brand awareness on purchasing decisions of Bittersweet by Najla, and to determine the effect of price and brand awareness on purchasing decisions of Bittersweet by Najla. This research is quantitative. Data collection techniques used questionnaires. The data analysis technique used is instrument test, classical assumption test, multiple linear regression, hypothesis testing, and the coefficient of determination. The results of the study show that price and brand awareness have a partial and simultaneous effect on purchasing decisions.